Integrasi Nilai Religius-Nasionalis KH Saifuddin Zuhri dalam Pembelajaran IPAS Kelas VI SD/MI - Hidayat, Fahri; Febriana, Maghfira (Dawuh Guru: Jurnal Pendidikan MI/SD, 2025)
This study aims to examine the integration of religious-nationalist values in the learning of Natural and Social Sciences (IPAS) at Islamic elementary schools (SD/MI), inspired by the thoughts of KH Saifuddin Zuhri. The study is motivated by the urgency of foundational education in shaping national character and spiritual awareness amid globalization and value crises. A qualitative approach was used through library research, analyzing KH Saifuddin Zuhri’s works and the IPAS curriculum in the Merdeka Curriculum. The findings indicate that the religious-nationalist paradigm advocated by KH Saifuddin Zuhri can serve as a conceptual model for integrative IPAS learning. This concept is relevant as it bridges Islamic values and patriotism within the themes of IPAS instruction. In conclusion, integrating religious-nationalist values not only enhances students' academic competence but also cultivates a moderate and nationally minded character aligned with the context of Islamic education in Indonesia